2021
DOI: 10.1302/2046-3758.107.bjr-2020-0234.r2
|View full text |Cite
|
Sign up to set email alerts
|

The effect induced by alternated mechanical loading on Notch-1 in mandibular condylar cartilage of growing rabbits

Abstract: Aims The aim of our study is to investigate the effect induced by alternated mechanical loading on Notch-1 in mandibular condylar cartilage (MCC) of growing rabbits. Methods A total of 64 ten-day-old rabbits were randomly divided into two groups according to dietary hardness: normal diet group (pellet) and soft diet group (powder). In each group, the rabbits were further divided into four subgroups by feeding time: two weeks, four weeks, six weeks, and eight weeks. Animals would be injected 5-bromo-2′-deoxyuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Abnormal biomechanical stimulation plays a key role in the pathogenesis of OA of the knee and hip, the most common clinical type 27–31 . The TMJ is subjected to biological force stimulation during mastication, and abnormal occlusion may lead to changes in the biological force environment borne by the TMJ, thereby inducing TMD or even TMJ OA 32–34 . In this study, we successfully induced OA‐like cartilage degeneration in TMJ through UAC to alter the biomechanical environment of TMJ in rats, further confirming the key role of occlusal abnormal factors in the pathogenesis of TMD and TMJ OA.…”
Section: Discussionsupporting
confidence: 67%
“…Abnormal biomechanical stimulation plays a key role in the pathogenesis of OA of the knee and hip, the most common clinical type 27–31 . The TMJ is subjected to biological force stimulation during mastication, and abnormal occlusion may lead to changes in the biological force environment borne by the TMJ, thereby inducing TMD or even TMJ OA 32–34 . In this study, we successfully induced OA‐like cartilage degeneration in TMJ through UAC to alter the biomechanical environment of TMJ in rats, further confirming the key role of occlusal abnormal factors in the pathogenesis of TMD and TMJ OA.…”
Section: Discussionsupporting
confidence: 67%
“…[27][28][29][30] The TMJ is subjected to biological force stimulation when exercising masticatory function, and abnormal occlusion may lead to changes in the biomechanical environment to which the TMJ is subjected, inducing TMD and even TMJ OA. [31][32][33] In this study, we successfully induced osteoarthritic cartilage degeneration in the TMJ by constructing UAC to change the biomechanical environment of the TMJ in mice, which confirmed the key role of occlusal abnormalities in the pathogenesis of TMD and TMJ OA.…”
Section: Discussionsupporting
confidence: 64%
“…A previous study showed that Notch signaling suppresses NFATc1 expression in ATDC5 cells and primary chondrocytes Zanotti and Canalis, 2013 . Furthermore, the Notch signaling can be activated by mechanical loading in mandibular condylar chondrocytes and bone marrow stromal cells Ziouti et al, 2019 ; Yan et al, 2021 . Therefore, it is possible that mechanical loading and Notch signaling act upstream of NFATc1 expression during articular cartilage development.…”
Section: Discussionmentioning
confidence: 99%